A biomolecule-assisted, cost-efficient route for growing tunable CuInS2 films for green energy application. Issue 33 (6th April 2017) - Frank, Anna; Wochnik, Angela S.; Bein, Thomas; Scheu, Christina
Abstract : A successful biomolecule-assisted, non-toxic solvothermal synthesis for CuInS2 on TCO substrate with desirable absorption behavior and band gaps is presented. Abstract : CuInS2 has become a popular and promising candidate as an absorber material in photovoltaic devices and photo-electrochemical cells. Here we report the successfull -cysteine-assisted growth of homogeneous, nanostructured CuInS2 thin films deposited on fluorine-doped tin oxide coated glass. In contrast to existing synthesis routes using thioacetamide as a sulfur source, our method offers the advantage of being environmentally friendly and non-toxic. We found thatl -cysteine is able to reduce the Cu 2+ ions of the precursor CuSO4 to Cu + in aqueous solution, thus enabling the formation of CuInS2 thin films. By varying the concentration of the reaction solution during the solvothermal synthesis route, we obtained CuInS2 films with different thicknesses and compositions, investigated with the help of energy dispersive X-ray spectroscopy with scanning and transmission electron microscopy. X-ray and electron diffraction experiments of the films prove the synthesis of a pure CuInS2 phase with the chalcopyrite structure except for the highestl -cysteine concentration where additional In2 S3 forms. UV-Vis absorption spectroscopy reveals absorption over the whole visible spectrum. The calculated band gap using the UV-Vis data ranges between 1.4 and 1.5 eV, and can be adjusted by changing crystal size and chemical composition. This offers a promising route towards tuning the optical and transport properties. First dye degradation experiments show promising activity under solar illumination.